AKSIOLOGI PENDIDIKAN KARAKTER BAGI KAUM MUDA REMAJA DI INDONESIA MENURUT PERSPEKTIF KI HAJAR DEWANTARA - Clemen Jaya Simbolon; Antonius Denny Firmanto (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This study aims to deepen the value and benefits of character education for young people, especially among adolescents who are generally seventeen years old. And its relevance in the lives of teenagers today. The character education of young people is a major issue in Indonesia today. This arises through a phenomenon that often occurs among adolescents and is quite disturbing to society. Some of the phenomena that arise are children becoming unable to accept other people's opinions openly and kindly, lack of listening to parental advice, becoming thugs and drug addicts. This is triggered by the lack of character education that should be built from an early age. If a child grows up in a harmonious, harmonious and peaceful condition and situation, of course the child will have a good character, be able to listen to parental advice, and will have dreams in the future. This situation will be compared upside down when the child gets the opposite or less good educational process. The method I use in this research is to conduct a critical analysis by examining character development in adolescence. As material in this reflection, I use some theories sourced from several books as references to help explain the meaning and importance of character education for young people. Through this study I came to the conclusion that character education plays a very important role in understanding and finding solutions for the good and bad tendencies of young people, especially adolescents.